RNA-based spatial community analysis revealed intra-reactor variation and expanded collection of direct interspecies electron transfer microorganisms in anaerobic digestion. (February 2020) - Guo, Bing; Zhang, Yingdi; Zhang, Lei; Zhou, Yun; Liu, Yang
Graphical abstract: Highlights: Fine spatial sampling revealed community variation along the height of sludge bed. Significantly different communities with and without GAC by RNA-based analysis. Active enrichments in complex GAC-biofilm expand potential DIET microorganisms. Bacteria Geobacter, Syntrophus, Desulfovibrio, and Blvii28 were enriched. Archaea Methanosaeta and Methanospirillum were enriched. Abstract: Granular activated carbon (GAC) has been shown to mediate direct interspecies electron transfer (DIET) in anaerobic digestion. Adding GAC to up-flow anaerobic sludge bed reactor increased the total biomass slightly from 20.0 to 26.6 gVSS/reactor, and maximum organic removal capacity remarkably from 285 to 1660 mgCOD/L/d. Since GAC occupied 7% of reactor volume (denser than suspended sludge, settled to the reactor bottom), we used a spatial sampling strategy (sludge bed top/mid/bottom layers, and tightly attached GAC-biofilm) and DNA- and RNA-based community analyses. RNA-based analysis demonstrated significant community differences between the non-GAC and GAC-amended reactors (p < 0.05) based on ANOSIM statistical analysis. In comparison, DNA-based analysis showed little community difference between these reactors (p > 0.05). RNA-based analysis revealed active enrichments in GAC-biofilm, including bacteria Geobacter, Syntrophus, Desulfovibrio and Blvii28, and archaea Methanosaeta and Methanospirillum . These are potential electro-active syntrophic microorganisms related with DIET, which expand the previously defined list of DIET microorganisms.